2018
DOI: 10.1038/s41438-018-0015-4
|View full text |Cite|
|
Sign up to set email alerts
|

Cytological, physiological, and transcriptomic analyses of golden leaf coloration in Ginkgo biloba L

Abstract: Ginkgo biloba is grown worldwide as an ornamental plant for its golden leaf color. However, the regulatory mechanism of leaf coloration in G. biloba remains unclear. Here, we compared G. biloba gold-colored mutant leaves and normal green leaves in cytological, physiological and transcriptomic terms. We found that chloroplasts of the mutant were fewer and smaller, and exhibited ruptured thylakoid membranes, indistinct stromal lamellae and irregularly arranged vesicles. Physiological experiments also showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 51 publications
(58 reference statements)
8
76
1
Order By: Relevance
“…Ultrastructural observations revealed that chloroplast development was prevented, and the structure was incomplete [32]. The GLK that regulates chloroplast development in the yellow leaves of G. biloba also exhibited downregulated expression [19]. Similarly, the GLK expression in the colored leaves was lower than that of green leaves, and further qRT-PCR also confirmed this result.…”
Section: Colored Leaves Are Closely Related To Chloroplast Dysplasiamentioning
confidence: 62%
See 2 more Smart Citations
“…Ultrastructural observations revealed that chloroplast development was prevented, and the structure was incomplete [32]. The GLK that regulates chloroplast development in the yellow leaves of G. biloba also exhibited downregulated expression [19]. Similarly, the GLK expression in the colored leaves was lower than that of green leaves, and further qRT-PCR also confirmed this result.…”
Section: Colored Leaves Are Closely Related To Chloroplast Dysplasiamentioning
confidence: 62%
“…The oil particles in the chloroplast increased and eventually disintegrated [27]. The ultrastructure of the colored leaves of Cymbidium sinense [16] and G. biloba [19] mutants was different from that of normal leaves, exhibiting a relatively low number of chloroplasts. The granum thylakoids had a low degree of overlap and loose arrangement, and the membrane structure was fuzzy.…”
Section: Colored Leaves Are Closely Related To Chloroplast Dysplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Ginkgo biloba L. is a landscape tree famous for its golden leaves in autumn. Previously, we found a novel golden-green striped leaf mutant and investigated the mutant leaves in cytological, physiological, and transcriptomic analyses (Li et al, 2018). Cytological and physiological experiments showed that the mutant had an abnormal ultrastructure in the chloroplast together with a lower chlorophyll content.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are only a few studies focus on the mechanism of yellow leaves. Leaf yellowing is generally considered to be caused by decreased Chl content, since Chl is the main pigment content of green leaves [2]. Therefore, studies of leaf yellowing have mostly focused on Chl biosynthesis and degradation.…”
Section: Introductionmentioning
confidence: 99%